Updated treatment of dementia with bosutinib: An open‐label study of a tyrosine kinase inhibitor. (31st December 2021) - Zielinski, Margaret A; Mahdavi, Kennedy D; Kuhn, Taylor P; Pereles, F. S; Bystritsky, Alexander; Whitney, Michael; Kesari, Santosh; O'Connor, Ed; Gross, Hyman; Barrows, Hannah R; Haroon, Jonathan; Habelhah, Barshen; et al.
Abstract: Background: A 2020 publication from Mahdavi and colleagues reported on clinical status changes observed among a sample of 31 older adults with neurodegenerative conditions who completed 12 months of bosutinib therapy. This abstract provides updated results for an additional 21 patients who have completed the 12‐month regimen since the time of the initial publication. This study pursues and updates data on an effective therapeutic intervention for dementia using TKI's such as bosutinib. Method: 52 patients with probable Alzheimer's dementia (AD) or Parkinson's spectrum disorder with dementia (PDD) completed 12 months of bosutinib therapy. The Clinical Dementia Rating scale (CDR) as estimated by the Quick Dementia Rating System (QDRS) was the primary cognitive status outcome measure. Results: For the updated sample size of 52 individuals who have completed the protocol, bosutinib was associated with improved CDR scores for 40% of participants (36% AD, and 46% PDD); bosutinib was also associated with clinically stable CDR scores for 38% of patients (36% AD, and 46% PDD). After completion of the protocol intervention, 29% of the AD population yielded decreased CDR scores while only 8% of PDD patients had decreased CDR scores. Conclusion: These results update findings from the previously reported study (Mahdavi et al., 2020) and continue to warrant further investigation of bosutinib as a potential therapeutic agent for dementia. The data continue to suggest an overall positive or stable outcome among participants after a year of bosutinib, with a clinical improvement rate of approximately 40% and a 38% rate of clinical stabilization. This observation remains consistent regardless of severity of cognitive impairment at baseline. We expect to report on an update for an additional 30 participants in the next year.